Insights into the sodiation mechanism of hard carbon-like materials from electrochemical impedance spectroscopy. Issue 19 (7th May 2021) - Schutjajew, Konstantin; Tichter, Tim; Schneider, Jonathan; Antonietti, Markus; Roth, Christina; Oschatz, Martin
Abstract : Electrochemical impedance spectroscopy combined with the analysis of the distribution of relaxation times is performed on a hard carbon sodium ion anode. Several electrokinetic processes are identified, and the sodium storage mechanism is elucidated. Abstract : To render the sodium ion battery (SIB) competitive among other technologies, the processes behind sodium storage in hard carbon anodes must be understood. For this purpose, electrochemical impedance spectroscopy (EIS) is usually undervalued, since fitting the spectra with equivalent circuit models requires an a priori knowledge about the system at hand. The analysis of the distribution of relaxation times (DRT) is an alternative, which refrains from fitting arbitrarily nested equivalent circuits. In this paper, the sodiation and desodiation of a hard carbon anode is studied by EIS at different states of charge (SOC). By reconstructing the DRT function, highly resolved information on the number and relative contribution of individual electrochemical processes is derived. During the sloping part of the sodiation curve, mass transport is found to be the most dominant source of resistance but rapidly diminishes when the plateau phase is reached. An equivalent circuit model qualitatively reproducing the experimental data of the sloping region was built upon the DRT results, which is particularly useful for future EIS studies on hard carbon SIB anodes. More importantly, this work contributes to establish EIS as a practical tool to directly study electrode processes without the bias of a previously assumed model.